2008
DOI: 10.1016/j.jfludis.2008.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Age of acquisition and repetition priming effects on picture naming of children who do and do not stutter

Abstract: The effects of age of acquisition and repetition priming on picture naming latencies and errors were studied in 22 children who stutter (CWS) and 22 children who do not stutter (CWNS) between the ages of 3;1 and 5;7. Children participated in a computerized picture naming task where they named pictures of both early and late acquired (AoA) words in two consecutive stages. Findings revealed that all children's picture naming latencies and errors were reduced following repetition priming and in response to early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 85 publications
7
40
0
Order By: Relevance
“…The latter point warrants further explanation. One well-documented finding from the language and memory literature is that adults and children tend to exhibit faster and more accurate performance on behavioral tasks with repeated presentations of the same or similar stimuli (e.g., Anderson, 2008). Thus, if the CWS were reacting to the language processing demands instead of inhibition, we should have seen a reliable improvement in their speed of performance across trials in the two tasks.…”
Section: Limitationsmentioning
confidence: 84%
“…The latter point warrants further explanation. One well-documented finding from the language and memory literature is that adults and children tend to exhibit faster and more accurate performance on behavioral tasks with repeated presentations of the same or similar stimuli (e.g., Anderson, 2008). Thus, if the CWS were reacting to the language processing demands instead of inhibition, we should have seen a reliable improvement in their speed of performance across trials in the two tasks.…”
Section: Limitationsmentioning
confidence: 84%
“…Pellowski and Conture (2005) found that CWS did not appear to benefit from semantic priming, and Burger and Wijnen (1998) reported that AWS showed weaker phonological priming than AWDNS (but see Burger & Wijnen, 1999, for some contradictory findings). While CWS seem to show generally similar phonological priming patterns to CWDNS (Melnick, Conture & Ohde, 2003), there are some subtle differences (Byrd, Conture, & Ohde, 2007), Likewise, Anderson (2008) found slight differences in identity priming for CWS (speeding response by re-presenting identical stimuli). These results suggest that the phonological representations of target words, or the links between semantic and phonological representations are less well specified in the mental lexicons of children who stutter (Anderson, 2008).…”
Section: Lexical Processing In People Who Stuttermentioning
confidence: 88%
“…While CWS seem to show generally similar phonological priming patterns to CWDNS (Melnick, Conture & Ohde, 2003), there are some subtle differences (Byrd, Conture, & Ohde, 2007), Likewise, Anderson (2008) found slight differences in identity priming for CWS (speeding response by re-presenting identical stimuli). These results suggest that the phonological representations of target words, or the links between semantic and phonological representations are less well specified in the mental lexicons of children who stutter (Anderson, 2008). This might imply that there would also be differential effects of phonological neighborhood characteristics on the word retrieval abilities of children who do and do not stutter.…”
Section: Lexical Processing In People Who Stuttermentioning
confidence: 88%
“…There are data to suggest that persons who stutter have less specified or rather less robust phonological representations (e.g. Byrd, Conture, & Ohde, 2007;Anderson, 2008;Anderson & Byrd, 2008). Thus, one could argue that it might take more time for PWS to complete the phonological spell-out.…”
Section: Theoretical Considerationsmentioning
confidence: 99%